Judicial Disputes Occurred in the Process of Reconstruction of Certain Class Employees - Khojaev Yunuskhoja Mustafokhoja ogli (Genius Journals, 2022)
This article describes the concept of certain categories of employees, labor disputes arising in the process of their reinstatement, the jurisdiction of labor disputes involving them, as well as errors and omissions in the practice of resolving labor disputes by the courts, suggestions and conclusions for their legal resolution
Keywords: civil servant; certain categories of employees; labor dispute; reinstatement